HUBUNGAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DENGAN KEJADIAN DIARE PADA ANAK USIA BALITA DI WILAYAH KERJA PUSKESMAS PUTRI AYU KOTA JAMBI - Winna Kurnia Sari AZ Winna; Sri Winingsih (Jurnal Nurse, 2023)
Diarrhea disease often affects infants and toddlers one of the most commonly studied risk factors are environmental factors that include clean water (SAB), environmental sanitation, jamban, and home conditions. This research aims to know the relationship of the behavior of clean and healthy life (PHBS) with the incidence of diarrhea in children of toddlers in the working area of Putri Ayu City Jambi in 2020. This research is a quantitative study with a cross centional approach. The population in this research is all mothers who have children in the workplace of the health center of Putri Ayu Jambi with a population of 655 people. The samples in this study were as many as 40 people with simple random sampling techniques. Univariate and bivariate data analysis. The results showed that from 40 respondents, as many as 24 respondents (60%) Diarrhea, giving the ASI exclusively as many as 23 respondents (57.5%), use of clean water is not eligible as much as 24 respondents (60%), do not wash with soap with 21 respondents (52.5%) and qualified for 22 respondents (55%). There is an exclusive breast-feeding relationship (P = 0,002) and soap-wearing handwash (P = 0,002) with the incidence of diarrhea with P value of < 0.05. There is no net use of water (P = 0,056) and the use of healthy latrines (P = 0,080) with the incidence of diarrhea with P value > 0.05.